Optimization of The Management of Severely Damaged Assets in DKI Jakarta Province - Fransisca Lola Mussilla (Jurnal Impresi Indonesia, 2025)
Asset replacement is carried out when the asset no longer supports government operations or public services, such as because it is obsolete, badly damaged, lost, or its economic useful life has expired. Assets that are no longer usable can be a burden in terms of benefits and finances if not immediately removed. This study discusses the management of badly damaged assets in the South Jakarta Administrative City which is still not optimal, and seeks strategies to improve the effectiveness of its management. The purpose of this study is to analyze obstacles and formulate strategies for managing badly damaged assets, with a focus on asset inventory and assessment, asset utilization, write-off methods, management performance evaluation, and asset information systems, using P.J. Barrett's theory. The study uses a qualitative descriptive method with document studies and interviews. The results of the study indicate that the write-off of Regional Property is in accordance with regulations, but there are still obstacles such as limited resources and the absence of a time limit for issuing write-off approvals, so that many badly damaged assets are still recorded as active. In addition, asset management is still manual because it is not supported by a technology-based information system, which causes the process to be slow. The recommended strategies include increasing the commitment of regional leaders, developing an integrated information system, improving the quality of human resources, and preparing regional regulations related to asset write-offs.